Assessment of Art Criticism Competency Needs of Students in the Art and Design Department of Guangxi University of Foreign Languages - Ming, Zhao; Qin, Jian (Academic MCU Buriram Journal, 2025)
The purpose of this article was to explore the views of students from the Art Design Department of Guangxi University of Foreign Languages on art criticism theory. Art criticism is one of the four fundamental disciplines of discipline-based art education. It refers to a systematic and organized approach to studying artworks through viewing and discussing art, involving the description, analysis, interpretation, and judgment of artworks. Through the studio practice of classroom art criticism activities, teachers in the design department organize students to interpret and evaluate their own art works, integrating art criticism theory with studio practice. This study uses 140 first-year graphic design students from GUFL as the experimental sample and employs Feldman's art criticism model to conduct critical analysis of artworks. The collected experimental data is analyzed quantitatively using descriptive statistical techniques. Scores are considered in the form of average scores and frequencies to determine students' performance in critical thinking skills. The Pearson correlation coefficient is used to calculate the correlation between students' studio practice and their scores in art critical thinking ability. Through brainstorming, questionnaires, and in-class tests, the current level of art criticism ability of 140 students is investigated. The research result found that: By explaining the importance of art criticism ability, students become aware of its significance, and a questionnaire is used to survey the expectations of 140 students regarding art criticism ability. By analyzing the current level and expectations of students' art criticism ability, the gap between them is identified. The findings of this study suggest that articulating the significance of art criticism competencies enables students to comprehensively recognize their importance. Furthermore, an analysis of the current status and contextual conditions of art criticism skills facilitates the derivation of informed conclusions. This approach provides a systematic framework for assessing students' needs, thereby enabling the development of effective models or strategies for art evaluation within art and design education programs.